The Influence of Product Quality, Brand Image and Digital Marketing on Purchasing Decision for Indomie Products in Banjarnegara - Susanti, Vina; Hidayah, Arini; Zamakhsyari, Luthfi (East Asian Journal of Multidisciplinary Research, 2024)
The purpose this study is to ascertain the influence of product quality, brand image and digital marketing on indomie purchasing decisions in Banjarnegara. This type of research use a quantitative approach using the purposive sample method, with the criteria of Indomie consumers and domiciled in Banjarnegara. There are 112 respondents as the sample .The result of partial test research show that purchase decisions are positively and significantly impacted by product quality, positively and significantly by brand image and positively and significantly by digital marketing. The simultaneous test shows that product quality, brand image and digital marketing have a positive and significant simultaneous influence on purchasing decisions. Research recommends improvements on the digital marketing variable by being more hostile in providing product information on digital media, so that Indomie reach is wider and consumers can recognize it.